Volume 6: Turbomachinery, Parts a and B 2006
DOI: 10.1115/gt2006-90738
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Layer Separation Control With Fluidic Oscillators

Abstract: Fluidic oscillating valves have been used in order to apply unsteady boundary layer injection to repair the separated flow of a model diffuser, where the hump pressure gradient represents that of the suction surface of a highly loaded stator vane. The fluidic actuators employed in this study consist of a fluidic oscillator that has no moving parts or temperature limitations and therefore is more attractive for implementation on production turbomachinery. The fluidic oscillators developed in this study generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Open-loop flow control strategies based on various actuator technologies [3]-such as plasma actuators [4][5][6], fluidic oscillators [7][8][9][10][11], and synthetic jets [12][13][14][15][16]-have been shown to effectively alter separated flows, and in some cases to even yield complete reattachment. In [17], oscillatory forcing was found to improve control authority for separation control.…”
Section: Introductionmentioning
confidence: 99%
“…Open-loop flow control strategies based on various actuator technologies [3]-such as plasma actuators [4][5][6], fluidic oscillators [7][8][9][10][11], and synthetic jets [12][13][14][15][16]-have been shown to effectively alter separated flows, and in some cases to even yield complete reattachment. In [17], oscillatory forcing was found to improve control authority for separation control.…”
Section: Introductionmentioning
confidence: 99%
“…Since the profile is supposed to be applicable over a wide Reynolds number range, an active flow control method was favoured. Comparing different active methods, several authors like Bons et al [6] and Cerretelli and Kirtley [7] reported that unsteady excitation of the boundary layer flow is much more efficient than, for example, steady blowing. Cerretelli and Kirtley [7] achieved with fluidic oscillators a 60% reduction of injection momentum combined with a 30% reduction in blowing power compared to optimal steady blowing in a diffuser test rig.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing different active methods, several authors like Bons et al [6] and Cerretelli and Kirtley [7] reported that unsteady excitation of the boundary layer flow is much more efficient than, for example, steady blowing. Cerretelli and Kirtley [7] achieved with fluidic oscillators a 60% reduction of injection momentum combined with a 30% reduction in blowing power compared to optimal steady blowing in a diffuser test rig. Different dimensionless frequencies were investigated by Cerretelli and Kirtley [7] following the work by Glezer et al [8] who investigated high frequency actuation with synthetic jet actuators.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations